The Aquaporin Splice Variant NbXIP1;1α Is Permeable to Boric Acid and Is Phosphorylated in the N-terminal Domain - Ampah-Korsah, Henry; Anderberg, Hanna I.; Engfors, Angelica; Kirscht, Andreas; Norden, Kristina; Kjellstrom, Sven; Kjellbom, Per; Johanson, Urban (Frontiers in Plant Science, 2016)
Aquaporins (AQPs) are membrane channel proteins that transport water and uncharged solutes across different membranes in organisms in all kingdoms of life. In plants, the AQPs can be divided into seven different subfamilies and five of these are present in higher plants. The most recently characterized of these subfamilies is the XIP subfamily, which is found in most dicots but not in monocots. In this article, we present data on two different splice variants (α and β) of NbXIP1;1 from Nicotiana benthamiana. We describe the heterologous expression of NbXIP1;1α and β in the yeast Pichia pastoris, the subcellular localization of the protein in this system and the purification of the NbXIP1;1α protein. Furthermore, we investigated the functionality and the substrate specificity of the protein by stopped-flow spectrometry in P. pastoris spheroplasts and with the protein reconstituted in proteoliposomes. The phosphorylation status of the protein and localization of the phosphorylated amino acids were verified by mass spectrometry. Our results show that NbXIP1;1α is located in the plasma membrane when expressed in P. pastoris, that it is not permeable to water but to boric acid and that the protein is phosphorylated at several amino acids in the N-terminal cytoplasmic domain of the protein. A growth assay showed that the yeast cells expressing the N-terminally His-tagged NbXIP1;1α were more sensitive to boric acid as compared to the cells expressing the C-terminally His-tagged isoform. This might suggest that the N-terminal His-tag functionally mimics the phosphorylation of the N-terminal domain and that the N-terminal domain is involved in gating of the channel.